Sex-specific association between atherogenic index of plasma and risk of newly diagnosed abdominal aortic aneurysm: a large population-based cohort study - Peng Qiu; Hongbin Guo; Chao Zhu; Yijun Liu; Jiazhen Zheng; Hongji Pu; Xinwu Lu; Qun Huang; Guang Liu; Kaichuang Ye; Zhen Zhou (European Journal of Medical Research)
Abstract Objectives Atherosclerosis of aortic wall has been suggested as a key pathological feature of abdominal aortic aneurysm (AAA). We conducted a first-ever prospective cohort study aiming at assessing the sex-specific association between atherogenic index of plasma (AIP) and risk of newly diagnosed AAA. Methods This study included 193,013 male and 226,785 female participants from the UK Biobank. AIP was calculated as a ratio of logarithmically transformed triglycerides to high-density lipoprotein-cholesterol. The outcome of interest was new AAA, identified by ICD-10 and OPCS-4 code, or by AAA-related death. All analyses were sex-stratified: Multivariable Cox proportional-hazard models were employed to assess the association between baseline AIP and AAA risk. Harrell’s c index was estimated to assess the value of AIP added to the discrimination of AAA prediction model. Results Over an average follow-up of 15.3 years, 1931 (1.00%) new AAA cases were recorded in males and 424 (0.19%) in females. In the fully adjusted models, compared with the bottom AIP quintile, HRs (95% CI) of newly diagnosed AAA was 1.67 (1.41, 1.96) in males and 1.75 (1.22, 2.52) in females within the top quintile. Subgroup analysis found smoking status significantly modified the association in females, with association existing only in female ever-smokers. Adding AIP into prediction model comprising age, smoking, and CVD history significantly improved the discrimination in males and male high-risk subgroups and in female ever-smokers (p < 0.05). Conclusions This study highlights the potential of AIP as a biomarker for AAA and its utility in identifying high-risk individuals qualified for AAA screening.